Effects of Leucaena pallida and Sesbania sesban supplementation on testicular histology of tropical sheep and goats - Woldemeskel, M.; Tegegne, Azage; Umunna, N.N.; Kaitho, R.J.; Tamminga, S. (Elsevier, 2001)
Thirty Ethiopian highland rams with an average body weight of 23.7 kg (S.D = 1.23) and age of 18 months and 25 East African bucks with an average body weight of 18.6 kg (S.D. = 2.06) and age of 14 months were used to study the long term effects of supplementation with the leaves of Leucaena pallida and Sesbania sesban on testicular histology. Within species, animals were blocked based on body weight and scrotal circumference and randomly assigned, within blocks, to five nutritional treatment groups in a complete randomised block design. All animals were provided with unchopped teff (Eragrostis tef) straw ad libitum and were supplemented with either 150g of wheat bran (control), leucaena (200 or 400 g) or sesbania (200 or 400 g) leaves for a period of 6 months. At the end of the experimental period, all animals were surgically castrated and testicular samples were collected and prepared for histopathological examination. In sheep 200 g S. sesban induced relatively more necrosis of the seminiferous tubules than 200 g L pallida, but with similar degree of tubular degeneration. However, lesions in testis of goats fed on 200 g S. sesban and 200 g L pallida did not differ. The effect of 400 g S. sesban and 400 g L pallida in sheep indicated that the former hardly induced lesions except depressive effect on spermatogenesis. Similar results were observed in goats. About 400 g S. sesban induced milder lesions in sheep and goats than were 200 g S. sesban. The lesions were compared and discussed in relation to the phytochemical composition of the supplementary feeds.